Predation by white-fronted capuchin monkeys, Cebus albifrons on eggs of three species of freshwater turtles in Brazilian Amazonia: solitary nests are also depredated. Issue 31 (18th August 2021) - Gentil, Eduardo; Bezerra, Bruna; Medeiros, Larissa A. de; Barnett, Adrian A.
ABSTRACT: Although freshwater turtles are well-known for group nesting, most species are solitary nesters, often deploying nest concealment to reduce egg predation risk. Records of predation on such taxa are much less common than on synchronously nesting species, most likely due to the scattered distribution and inconspicuousness of such nests. Here, we report depredation in Jaú National Park, Amazonas, Brazil, by a diurnal generalist Neotropical primate (White-fronted capuchin, Cebus albifrons ), on nests of three freshwater turtle species ( Kinosternon scorpioides, Peltocephalus dumerilianus, both obligate solitary nesters, and Podocnemis erythrocephala, which does so facultatively). The species involved were identified by distinct characteristics of the eggs and nests (turtles), and impressions of the hands and feet (primates). While the current report shows that nests are subject to predation by generalist species such as white-fronted capuchins, the extent to which this impacts local turtle populations remains unclear. Further studies should address whether or not this is a general phenomenon or the result of a local foraging strategy by the primate concerned. Field-based, preferably long-term, studies are recommended to answer such questions.